On the radial monotonicity of the ensemble average propagator - Bodur, Erkam. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
The ensemble average propagator (EAP) is the di usion propagator averaged over a volume of porous medium. This mathematical tool contains substantial amount of information concerning the geometry of the underlying structure. It is possible to measure the EAP via di usion NMR methods which makes it relevant for many characterization studies. However, the mathematical properties of the EAP have not been fully studied and well-understood. In this thesis, we study the loss of radial monotonicity of the average propagator.
Keywords: Averaging method (Differential equations)